Development of a sensitive and specific nanoparticle‐assisted PCR assay for detecting HPV‐16 and HPV‐18 DNA. Issue 12 (10th May 2020) - Ma, Xingjie; Li, Yucheng; Liu, Ranran; Wei, Wenping; Ding, Changping
Abstract: Carcinoma precursor lesion caused by persistent infection of human papillomavirus (HPV) types 16 and 18 is known as a principal inducer of cervical cancer. Therefore, rapid and effective detection of HPV‐16 and HPV‐18 infection at early stage is an important strategy for preventing such disease. In this study, a novel duplex nanoparticle‐assisted polymerase chain reaction (nanoPCR) assay was developed to detect both of the two genotypes simultaneously. Two pairs of primers for nanoPCR were designed based on the conserved region within the early 6 (E6) gene of HPV‐16 and HPV‐18, respectively. After optimizing reaction conditions, the nanoPCR assay displayed 10‐fold more sensitive than that of conventional PCR and showed high specificity. The detection limit of nanoPCR was 1.7 × 10 1  copies/μL for HPV‐16, 1.2 × 10 2  copies/μL for HPV‐18, and no cross‐reaction was detected after using other viruses or HPV subtypes as templates. Of 209 clinical samples collected from patients, as also confirmed by sequencing, the nanoPCR method gave consistent results with conventional PCR assay: 7 positives for HPV‐16, 4 positives for HPV‐18, and no co‐infection. Here is the first report to introduce a reproducible nanoPCR assay for detecting HPV DNA with high sensitivity and specificity, which may point out a useful diagnostic tool for potential clinical application. Highlights: A novel nanoPCR method was developed for the detection of HPV‐16 and HPV‐18. The HPV nanoPCR assay was 10‐fold more sensitive than conventional PCR assay. The lower detection limit was 1.7 × 101 copies/μL for HPV‐16 and 1.2 × 102 copies/μL for HPV‐18.